Third‐Generation Covalent TMP‐Tag for Fast Labeling and Multiplexed Imaging of Cellular Proteins. Issue 36 (29th July 2022) - Mo, Jiaming; Chen, Jingting; Shi, Yabo; Sun, Jingfu; Wu, Yunxiang; Liu, Tianyan; Zhang, Junwei; Zheng, Yu; Li, Yulong; Chen, Zhixing
Abstract: Self‐labeling protein tags can introduce advanced molecular motifs to specific cellular proteins. Here we introduce the third‐generation covalent TMP‐tag (TMP‐tag3) and showcase its comparison with HaloTag and SNAP‐tag. TMP‐tag3 is based on a proximity‐induced covalent Michael addition between an engineered Cys of E. coli dihydrofolate reductase (eDHFR) and optimized trimethoprim (TMP)–acrylamide conjugates with minimal linkers. Compared to previous versions, the TMP‐tag3 features an enhanced permeability when conjugated to fluorogenic spirocyclic rhodamines. As a small protein, the 18‐kD eDHFR is advantageous in tagging selected mitochondrial proteins which are less compatible with bulkier HaloTag fusions. The proximal N−C termini of eDHFR also enable facile insertion into various protein loops. TMP‐tag3, HaloTag, and SNAP‐tag are orthogonal to each other, collectively forming a toolbox for multiplexed live‐cell imaging of cellular proteins under fluorescence nanoscopy. Abstract : The third‐generation TMP‐tag3 is developed. It features optimized synthesis, fluorogenic labeling, and fast cellular intake. It performs well in comparative studies with HaloTag and SNAP‐tag. The 18 kD‐protein tag is compatible with loop insertion. The TMP‐tag3 supplements and supplants the existing self‐labeling protein tags, adding an orthogonal channel for multiplexed labeling and nanoscopic imaging.